Using Wordless Picture Book as a Contributive Learning Media to Enhance the Student's Writing Ability - Khadijah Maming; Irmayanti Irmayanti; Rafi'ah Nur (EDUVELOP, 2019)
This research aims to know enhancement the Student's writing ability by using wordless picture book as a contributive learning media. The benefits of using wordless picture book show that the students enhance their writing ability and create their creative writing and thinking skill. The researcher applied quasi-experimental method, with two groups namely experimental and control class. The experimental class consists of 30 students and control clas consists of 30 students. The subjects of the research were 60 students from two classes taken from students of SMP Negeri 10 Parepare. The research instrument was writing test in which the comparison of pre-test and post-test decided the enhancement of the Student's writing ability. The results of the data analysis showed that the Student's writing ability getting significantly improvement. It was proved by the mean score of pre-test was 46.93 and the post-test was 80.00. It indicates that the use of wordless picture book can enhance the Student's writing ability at SMP Negeri 10 Parepare. Besides, after analyzing the data by using the t-test formula, the result of t-test value in post-test was 6.02 and t-table value was 1.671. It meant that the t-test value was higher than t-table value. It clarified H1 was accepted and H0 was rejected and the students who were taught by using wordless picture book were better than the students who were taught by using wordless picture book.